SPIRITUAL IMBALANCES IN THOMAS WOLFE’S LOOK HOMEWARD, ANGEL: A BINARY OPPOSITES ANALYSIS - Ruibai, Sun; Ambigapathy, Pandian; Collin, Jerome (2023)
Thomas Wolfe is a renowned writer of the 20th century, and his work Look Homeward, Angel features characters with complex personalities. This paper examines the spiritual imbalances of these characters using the theory of binary opposites, which highlights the contradictions within the protagonist Eugene and his family. The binary opposites include good versus evil, love versus hate, fantasy versus reality, spirit and material, etc. The analysis shows that the characters experience spiritual imbalances in different ways, including mental numbness, the materialization of spirit, and the self-splitting of the psyche. The study also explores the underlying causes of these imbalances, such as the commodification and alienation of individuals’ spirits during the transformation of America’s social economy in the 1920s. By providing a deeper understanding of the character’s inner struggles, this paper sheds light on America’s disoriented and perplexed spiritual state during the post-WWI era.